Coastal environmental assessment for tourism development of San Vicente, Palawan seagrass component - Bitara, Arselene U. (University Journal: the official journal of Palawan State University, 2015)
This study presents the results of the seagrass assessment conducted at Long Beach, a 14-kilometer tourist attraction at San Vicente, Palawan, Philippines. The assessment identified seven species of seagrass belonging to six genera and two families in a patch of less than a hectare. The most frequently encountered is Cymodocea serrulata. Syringodium isoetifolium has the highest shoot density while Enhalus acoroides is least. Most fishes are found in the seaward seagrass edge.